2020
DOI: 10.3390/ijms21031059
|View full text |Cite
|
Sign up to set email alerts
|

Novel ACE Inhibitory Peptides Derived from Simulated Gastrointestinal Digestion in Vitro of Sesame (Sesamum indicum L.) Protein and Molecular Docking Study

Abstract: The aim of this study was to isolate and identify angiotensin I-converting enzyme (ACE) inhibitory peptides from sesame protein through simulated gastrointestinal digestion in vitro, and to explore the underlying mechanisms by molecular docking. The sesame protein was enzymatically hydrolyzed by pepsin, trypsin, and α-chymotrypsin. The degree of hydrolysis (DH) and peptide yield increased with the increase of digest time. Moreover, ACE inhibitory activity was enhanced after digestion. The sesame protein digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 55 publications
5
44
2
Order By: Relevance
“…Similarly, Aluko and Monu 11 also found that the filtrate from a 5000 MWCO membrane of the quinoa protein concentrate digested by Alcalase showed higher ACE inhibitory activity than the retained fraction. Research on other food protein hydrolyzates, such as sesame, 20 Antarctic krill, 21 and Kluyveromyces marxianus , 22 also found that a fraction with lower MW peptides exhibited stronger activity on ACE inhibition than fractions with higher MW peptides. The ultrafiltration membrane provides a cost‐effective way to concentrate bioactive peptides based on molecular weight distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Aluko and Monu 11 also found that the filtrate from a 5000 MWCO membrane of the quinoa protein concentrate digested by Alcalase showed higher ACE inhibitory activity than the retained fraction. Research on other food protein hydrolyzates, such as sesame, 20 Antarctic krill, 21 and Kluyveromyces marxianus , 22 also found that a fraction with lower MW peptides exhibited stronger activity on ACE inhibition than fractions with higher MW peptides. The ultrafiltration membrane provides a cost‐effective way to concentrate bioactive peptides based on molecular weight distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Seed storage proteins are the major proteins in the five seeds and are likely to be the main sources of bioactive peptides upon oral consumption and GI digestion. The nutritional values and the bioactivity of peptides derived from the five seeds have been reported ( Bao et al., 2020 ; Guo et al., 2020 ; Han et al., 2019 ; Innocent-Ukachi, 2019 ; Vilcacundo et al., 2018 ; Wang et al., 2020b ). Currently, there is still no effective approved treatment or vaccine that can be used to tackle or prevent COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive peptide produced from sesame seed protein by enzymatic hydrolysis is an essential branch in sesame seed protein processing. Previous research has found that sesame seed protein is the precursor of ACEinhibitory peptides (Chatterjee et al, 2015;Nakano et al, 2006;Wang et al, 2020). So far, sesame seed protein hydrolyzed by thermolysin, papain, pepsin, alcalase showed ACE-inhibitory activity (Chatterjee et al, 2015;Nakano et al, 2006), but choosing the proper protease to hydrolyze sesame seed protein and establishing optimal hydrolysis conditions are overlooked.…”
Section: Introductionmentioning
confidence: 99%